Socioeconomic status moderate the relationship between mental health literacy, social participation, and active aging among Chinese older adults: evidence from a moderated network analysis - Yalian Huang; Aibao Zhou; Ping Tang; Xufeng Ma (BMC Public Health)
Abstract Objective The aging population represents a formidable global challenge, with China experiencing an accelerated demographic shift. While previous research has established a directional link between mental health literacy, social participation, and active aging, the moderating effect of socioeconomic status (SES) on these associations remains underexplored. This study sought to address this gap by employing moderated network analysis, in contrast to the total score approaches commonly used in prior literature. Methods A cross-sectional design was implemented, involving 1,032 Chinese individuals aged 60 and above, who completed the Mental Health Literacy Questionnaire, Active Aging Scale, Social Participation Questionnaire, and Socioeconomic Status Index Scale. The moderated network method was applied to explore the bidirectional relationships between mental health literacy, social participation, and active aging, while examining the moderating role of SES. Results The analysis identified the strongest bidirectional relationships between attitudes toward mental illness and the development of spiritual wisdom. Seven interaction terms emerged involving mental health literacy, social participation, and active aging, moderated by SES. Notably, the most significant interaction terms were found between attitudes toward mental illness and engagement in active learning. Conclusions These results contribute novel insights into the bidirectional relationships among mental health literacy, social participation, and active aging, as well as the role of SES in moderating these relationships. The findings highlight the need for targeted policy interventions to address socioeconomic inequalities in later life, thereby fostering active aging.